INFLUENCE OF FERTILIZATION AND QUALITY OF WATER IRRIGATION ON GROWTH AND DEVELOPMENT OF LETTUCE PLANTS - GALBIATTI, João Antonio; CAVALCANTE, Ítalo Herbert Lucena; RIBEIRO, Adriano Gerim; BECKMANN, Márkilla Zunete (Scientia Agraria, 2007)
The present work had as objective to evaluate the effects of different fertilizers and quality of water irrigation on growth and development of lettuce plants. It was used a completely randomized blocks design, and the treatments were distributed in a factorial arrangement 5 x 2, corresponding to fertilizing (no fertilizing, biofertilizer, bovine manure, poultry litter, mineral fertilizer) and quality of water irrigation, with 3 repetitions. Plant height, stem diameter, fresh and dry matter production and leaf area were evaluated. Treatments had statistical influence on fresh and dry matter production with lower results for non fertilized. There is no difference among fertilizers in relation to plant growth. The quality of water irrigation do not affected plant development.